Biblical Bestiary: Donkey (The Biblical archaeology review, 2020)
Donkeys get little to no respect. They are the popular embodiment of stubbornness and stupidity, and people of many languages invoke them as an insult. Its alternative appellation, ass, can hardly be helpful in improving the donkey’s image.